Utopia - Pilger, John (United Kingdom : Network Distributing, 2013)
Drawing on John Pilger's long association with the first people of his homeland, Australia, Utopia is both an epic portrayal of the oldest continuous human culture, and an investigation into a suppressed colonial past and rapacious present.
Keywords: Documentary films